COLLABORATIVE GOVERNANCE IN ENHANCHING SURABAYA'S TOURISM THROUGH SISTER CITY COOPERATION - SEPTIANA, AULIA DWI (PETA - Jurnal Pesona Pariwisata, 2022)
This research was written to analyze the collaboration of actors involved in sister city cooperation between Surabaya City and Kitakyushu City in developing Ecotourism Mangrove Wonorejo to become one of the tourist destinations that can contribute to improving Surabaya's tourism sector during the COVID-19 pandemic. As previously known, since the COVID-19 pandemic there have been many sectors affected and caused losses, one of which is the tourism sector. Surabaya city is one of the cities whose tourism sector development is also affected by the COVID-19 pandemic, this is evidenced by the many tourism destinations of Surabaya city that were closed during the COVID-19 pandemic, one of which is Ecotourism Mangrove Wonorejo. Although closed, when the easing of PPKM Ecotourism Mangrove Wonorejo is one of the tourist destinations that opened and became an alternative tourist destination during the COVID-19 pandemic. In the study that uses qualitative research methods with the use of the concept of Collaborative Governance and Sister City, the results of this study will explain the collaboration between the Surabaya City Government, Kitakyushu City Government, private parties, the public, and agencies / academics in realizing the improvement of surabaya tourism sector during the COVID-19 pandemic through wonorejo mangrove forest ecotourism. Keywords: Collaborative Governance, Surabaya City, Tourism, Sister City